Sophie Someone - Long, Hayley, 1971- (Somerville, Massachusetts : Candlewick Press, 2017)
Fourteen-year-old Sophie makes a startling discovery about her identity and family after questions about why her family suddenly moved to Belgium arise.
Keywords: Identity -- Fiction; Family life -- Fiction; Family secrets -- Fiction; Identity (Psychology) -- Fiction; Family life -- Fiction; Secrecy -- Fiction